Incidence of atrial and ventricular arrhythmias in obese patients with heart failure with reduced ejection fraction treated with sacubitril/valsartan - Abumayyaleh, Mohammad S. A.; Demmer, Jonathan; Krack, Carina; Pilsinger, Christina; El-Battrawy, Ibrahim; Aweimer, Assem; Lang, Siegfried; Mügge, Andreas; Akın, Ibrahim (Diabetes, obesity and metabolism, 2023)
Abstract Aim To compare clinical outcomes among patients with heart failure and reduced ejection fraction (HFrEF) according to body mass index (BMI) after initiating treatment with an angiotensin-receptor neprilysin inhibitor (ARNI). Methods We gathered data from 2016 to 2020 at the University Medical Center Mannheim; 208 consecutive patients were divided into two groups according to BMI.
Online veröffentlicht: 7. Juli 2023
Gesehen am 14.05.2024